Did the COVID-19 pandemic change the weight reduction in patients with obesity after bariatric surgery? - Somayeh Mokhber; Ali Sheidaei; Shahrzad Ahmadkaraji; Seyed Amin Setarehdan; Seyed Mohsen Rahimi; Fatemeh Sadat Hosseini-Baharanchi; Ali Mazaherinezhad; Abdolreza Pazouki (BMC, 2023)
Abstract Background The COVID-19 pandemic has significantly impacted healthcare services worldwide, including bariatric surgery. There is a concern that the pandemic-induced stay-at-home orders and social restrictions may negatively affect weight reduction outcomes post-bariatric surgery. This study aimed to examine the impact of the COVID-19 on weight loss up to six months after three types of bariatric surgeries including One-Anastomosis Gastric Bypass (OAGB), RY Gastric Bypass (RYGB), and Sleeve Gastrectomy (SG) before and two time periods during the COVID-19 pandemic. Methods We conducted a retrospective study using data from a comprehensive database of bariatric surgery patients in Iran. We recruited 882 patients who underwent bariatric surgery from the initiation of COVID-19 to 6 months before public vaccination (Time period 3); among them, 311 patients underwent surgery in the first six months of the pandemic (Time period 2). These patients were compared with 1368 ones in the control group who completed their 6 months follow-up before the pandemic. The study compared the BMI reduction, excess weight loss (EWL), and total weight loss (TWL) outcomes between these groups using Generalized Estimating Equations (GEE) with gamma distribution to adjust for factors that were unevenly distributed across the groups. Results The age of participants in time periods 2 and 3 had a mean (standard deviation) of 38.97 (10.99) and 38.84 (10.71), respectively. In all groups, the majority of patients were females, accounting for 76.02%, 71.06%, and 75.74% for the control group and time periods 2 and 3, respectively. There was no significant difference between the groups in terms of weight reduction, as measured by BMI reduction, EWL, and TWL (related P values: 0.283, 0.465 and 0.169). Regression analysis indicated that higher baseline BMI values were associated with greater BMI reduction (0.04, 95% CI: 0.03-0.05), but this did not translate to higher EWL or TWL. Males showed greater BMI reduction (0.33, 95% CI: 0.18-0.49) and EWL (1.58, 95% CI: 0.79-2.37) than females, while females achieved higher TWL compared to males. Among different types of surgery, the OAGB resulted in more weight reduction among patients in the study. Conclusion In conclusion, our study reveals that bariatric surgery remains effective for weight reduction during the first 6 months of the pandemic in Iran. Implementation of pandemic protocols ensures comparable efficacy to non-pandemic times. However, caution is needed in generalizing results beyond our specific context due to study limitations. Further research is essential to comprehensively assess the pandemic's broader impact on bariatric surgery outcomes under varying conditions.